Subjective wellbeing and intergenerational mobility of youths in Singapore - HO, Kong Weng (Institutional Knowledge at Singapore Management University, 2022)
Singapore has been enjoying persistently high real growth rates for the past 6 decades. On average, real per capita Gross Domestic Product (GDP) has grown from S$5603 in 1961 to S$88991 in 2019 with an average annual real per capita growth rate of 4.88%. The mean number of years of schooling for residents aged 25 and over has increased from 3.1 (Barro & Lee, 2001) in 1960 to 11.2 in 2019 while the life expectancy at birth for residents has also increased from 62.9 years in 1960 to 83.6 in 2019 (Department of Statistics, 2019). Although these figures reflect trneds of the broader population, we can infer that the growth in human capital over the years have brought about better health and higher educational achievement of the youths in Singapore. While economic wellbeing continues to improve in Singapore in the long-term, the subjective wellbeing of youths might be affected by short-run fluctuations in economic business cycles, diminishing growth opportunities and economic shocks, as well as other non-economic variables. Economic prosperity does contribute to the wellbeing of youths in Singapore; however, we are interested to find out the non-economic contributors to the wellbeing of youths, especially during the current pandemic when economic conditions and indicators have taken a dip, at least for the time being, and perhaps for the uncertain future. This chapter will investigate the roles of non-economic variables such as relationship stocks, life aspirations, and perceived opportunities in influencing the subjective wellbeing of youths in Singapore, using data from the National Youth Survey (NYS) 2019.